Potential bioinoculants for sustainable agriculture prospected from ferruginous caves of the iron Quadrangle/Brazil - Lemes, Camila G. C.; Cordeiro, Isabella F.; de Paula, Camila H.; Silva, Ana K.; Do Carmo, Flávio F.; Kamino, Luciana H. Y.; Carvalho, Flávia M. S. [UNESP]; Caicedo, Juan C.; Ferro, Jesus A. [UNESP]; Moreira, Leandro M. (MDPI, 2021)
Biocontrol and plant growth-promoting bacteria (PGPB) are important agricultural bioinoculants. This study aimed to prospect new potential bioinoculants for a more sustainable agriculture from ferruginous caves of the Brazilian Iron Quadrangle. Culturable bacteria, from seven caves and one canga soil sample, were evaluated for biocontroller activity of the phytopathogens Xanthomonas citri subsp. Citri—Xcc306 (citrus canker), Fusarium oxysporum—Fo (fusariosis), and Colletotrichum lindemuthianum—Cl89 (bean anthracnose). The ability of the superior candidates to solubilize inorganic phosphate, fix nitrogen, and produce hydrolytic enzymes and siderophores was then analyzed. Out of 563 isolates, 47 inhibited the growth of Xcc306 in vitro, of which 9 reduced citrus canker up to 68% when co-inoculated with the pathogen on host plants. Twenty of the 47 inhibited Fo growth directly by 51–73%, and 15 indirectly by 75–81%. These 15 inhibited Cl89 growth in vitro (up to 93% directly and 100% indirectly), fixed nitrogen, produced proteases and siderophores, showed motility ability, produced biofilm, and all but one solubilized inorganic phosphate. Therefore, 15 (2.66%) bacterial isolates, from the genera Serratia, Nissabacter, and Dickeya, act simultaneously as biocontrollers and PGPBs, and could be important candidates for future investigations in planta as an alternative to minimize the use of pesticides and chemical fertilizers through sustainable agricultural management practices.
Keywords: Bacterial prospecting; Bioinoculants; Ferruginous caves; Plant growth promoters